The Comparison Between Results of Trabeculectomy With and Without Prior Anti-Vascular Endothelial Growth Factor In Patients With Neovascular Glaucoma at Undaan Eye Hospital Surabaya, Indonesia - Malika, Rosalia Adriani; Nuradianti, Lydia (Universitas Airlangga, 2024)
Introduction: New intraocular medication and anti-vascular endothelial growth factor (VEGF) agents have been developed to manage neovascular glaucoma and surgery. However, no studies compare trabeculectomy with anti-VEGF to no anti-VEGF treatment in patients with neovascular glaucoma. Purpose: This study compares the decrease of intraocular pressure (IOP) between trabeculectomy with and without anti-VEGF in neovascular glaucoma. Methods: This observational study comprised 30 medical records of neovascular glaucoma, divided into 15 medical records of patients with anti-VEGF before trabeculectomy and medical records of patients operated with trabeculectomy without anti-VEGF, monitored between January 2021 and December 2021. Patients with incomplete medical records were excluded. Data collected are age, gender, risk factor, IOP preoperative, and during six months of follow-up IOP postoperative. Data analysis uses an Independent T-test and Mann-Whitney test. Results: From 30 samples, the mean IOP in trabeculectomy with the anti-VEGF group generally is 12.26 mmHg. Meanwhile, the mean IOP in trabeculectomy without the anti-VEGF group generally is 16.74 mmHg. The comparison between two groups shows that there are significant mean differences between them during 1-5 months follow-up (1 month: p = 0.022; 2 months: p = 0.007; 3 months: p = 0.007; 4 months: p = 0.042; and 5 months: p = 0.029). Conclusions: Trabeculectomy with prior administration of intravitreal anti-VEGF shows good IOP reduction and can be implemented in neovascular glaucoma (NVG) patients.